2021
DOI: 10.2196/18048
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Web-Based Sharing and Viewing of Self-Harm–Related Videos and Photographs on Young People: Systematic Review

Abstract: Background Given recent moves to remove or blur self-harm imagery or content on the web, it is important to understand the impact of posting, viewing, and reposting self-harm images on young people. Objective The aim of this study is to systematically review research related to the emotional and behavioral impact on children and young people who view or share web-based self-harm–related videos or images. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
0
11
0
2
Order By: Relevance
“…Protective or positive influences associated with self-harm-related content online have also been reported, such as access to social support (Bell, 2014;Daine et al, 2013;Lewis & Seko, 2016;Marchant et al, 2017Marchant et al, , 2021Robinson et al, 2016). In the last few years, guidelines to help young people communicate safely about suicide on social media have been developed (Robinson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protective or positive influences associated with self-harm-related content online have also been reported, such as access to social support (Bell, 2014;Daine et al, 2013;Lewis & Seko, 2016;Marchant et al, 2017Marchant et al, , 2021Robinson et al, 2016). In the last few years, guidelines to help young people communicate safely about suicide on social media have been developed (Robinson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Findings from several studies have raised concerns that self‐harm and suicidal content viewed online or on social media, particularly ‘graphic’ images or videos, may be harmful; for example, by normalising self‐harm and discouraging help‐seeking (Baker & Lewis, 2013; Bell, 2014; Brennan et al., 2022; Daine et al., 2013; Jacob, Evans, & Scourfield, 2017; Lewis, Heath, Sornberger, & Arbuthnott, 2012; Lewis & Seko, 2016; Marchant et al., 2017; Marchant, Hawton, Burns, Stewart, & John, 2021). The potential for harm is particularly concerning because self‐harm and suicide‐related internet sites are commonly accessed by young people engaging in self‐harm and are associated with both increased self‐harm and suicidal intent (Daine et al., 2013; Mars et al., 2015; Padmanathan et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The use of content warnings relates to other safety-driven initiatives. A recent systematic review investigating removal or blurring of self-harm online imagery found parallel issues of potential harm and positive impacts [ 40 ], reinforcing that research in content warnings and cognate areas is complex. There is a need to move beyond the current somewhat simplistic focus on whether content warnings help or harm towards a contextualised understanding of the mechanisms by which content warnings impact on recipients with different characteristics in different sectors and when used for different purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Как и предполагалось, воздействие самоповреждений в «Instagram» во время первой волны исследования проспективно предсказывало результаты, связанные с членовредительством и суицидом, во второй волне через 1 месяц. эти результаты свидетельствуют о том, что такое воздействие может привести к заражению уязвимых пользователей и подтверждаются публикациями других исследователей [71,72].…”
Section: влияние средств массовой информацииunclassified